Perilaku Penggunaan Alat Pelindung Diri pada Petani Sayur - Gracia Victoria Souisa; Claudya A Lekatompessy; Adriana Ritje Nendissa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Farmers in the processing of land and plants need pesticides to eradicate pests and weeds. Pesticide is a material that has many benefits for the sustainability of the world of agricultural production. Many plant destruction organisms that can reduce yields can be minimized with pesticides, but on the other hand, pesticides can harm the health of the farmers. To prevent the danger of using pesticides against self-purification, one must use personal protective equipment (PPE) in a complete and precise manner. The purpose of this research is to determine what are the factors related to the use of personal protective equipment on pesticide user farmers in Taeno village in 2019. This research is analytical research with a cross-sectional approach. This research sample amounted to 105 farmers—data collection using questionnaires, interviews, and observation. The data obtained is then processed with a statistical test of chi-square. Based on statistical test bivariate of knowledge variables associated with APD, the attitude variables are not associated with the use of the PPE, and the action variables are associated with the use of the PPE. The results showed that the variables associated with PPE use are variable knowledge (ρ = 0.025) and action variables (ρ = 0.015). The unrelated variables are the attitude variables (ρ = 0.137)—knowledge and action variables associated with PPE use.